1 views

Uploaded by Louis Guy

- 116geomtg
- Algebra Cheat Sheet
- Fis Algebra
- Workbook in Higher Algebra
- 116rationaltg
- 116sci not
- 314ssak
- Sapiens: A Brief History of Humankind
- The Unwinding: An Inner History of the New America
- The Subtle Art of Not Giving a F*ck: A Counterintuitive Approach to Living a Good Life
- Never Split the Difference: Negotiating As If Your Life Depended On It
- Shoe Dog: A Memoir by the Creator of Nike
- Maybe You Should Talk to Someone: A Therapist, HER Therapist, and Our Lives Revealed
- Hidden Figures: The American Dream and the Untold Story of the Black Women Mathematicians Who Helped Win the Space Race
- Elon Musk: Tesla, SpaceX, and the Quest for a Fantastic Future
- Yes Please
- John Adams
- Grit: The Power of Passion and Perseverance
- Devil in the Grove: Thurgood Marshall, the Groveland Boys, and the Dawn of a New America
- A Heartbreaking Work Of Staggering Genius: A Memoir Based on a True Story

You are on page 1of 2

Quadratic Functions

Basic Quadratic Function: y = x 2

parabola

vertex

Standard Form: y = a (x − h ) + k

2

“a”:

• If “a” is negative, function opens down.

• If “a” is positive, function opens up.

• If “a” is greater than 1, parabola gets skinnier.

• If “a” is less than 1, parabola gets wider.

“h”: Translates function horizontally.

“k”: Translates function vertically.

VERTEX = (h, k )

* “h” value always opposite sign!!

Axis of symmetry at x = h

EX:

y = 2( x + 3) − 1

2

x = -3

44

Mathematics 334 Designed by Peter Nield Notes by Katherine Daignault

Westwood High School Grade 9 Student

General Form: y = ax 2 + bx + c

“a”:

• If “a” is negative, function opens down.

• If “a” is positive, function opens up.

• If “a” is greater than 1, parabola gets skinnier.

• If “a” is less than 1, parabola gets wider.

“c”: the “y” intercept.

Converting Forms:

To convert general to standard form, you can complete the square.

EX:

y = 2 x 2 − 8 x + 12

(

y = 2 x 2 − 4x + 6 )

y = 2(x 2

− 4x + 4 − 4 + 6 )

[

y = 2 (x − 2) + 2

2

]

y = 2( x − 2) + 4

2

(

SHORTCUT: ax 2 + bx + c )

a=a

−b

h=

2a

4ac − b 2

k=

4a

EX:

y = 2 x 2 − 8 x + 12 a=2

b = −8

c = 12

y = a( x − h ) + k

2

a=a=2

−b 8

h= = =2

2a 4

4ac − b 2 4 × 2 × 12 − (− 8) 96 − 64

2

k= = = =4

4a 4× 2 8

y = 2( x − 2) + 4

2

45